2010
DOI: 10.1016/j.neuroscience.2010.02.071
|View full text |Cite
|
Sign up to set email alerts
|

Noise trauma impairs neurogenesis in the rat hippocampus

Abstract: The hippocampus, a major site of neurogenesis in the adult brain, plays an important role in memory. Based on earlier observations where exposure to high-intensity noise not only caused hearing loss but also impaired memory function, it is conceivably that noise exposure may suppress hippocampal neurogenesis. To evaluate this possibility, nine rats were unilaterally exposed for 2 h to a high-intensity, narrow band of noise centered at 12 kHz at 126 dB SPL. The rats were also screened for noise-induced tinnitus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
138
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 162 publications
(161 citation statements)
references
References 86 publications
(95 reference statements)
16
138
0
7
Order By: Relevance
“…As shown in Figure 2, the overall fluctuations of (G + S)/S ratios were not significantly different (F(4,50)=0.14, p=0.966) when measured at different time points. Consistent with other studies, our control group of mice exhibit robust gap-induced inhibition of the startle response (Turner et al 2006;Yang et al 2007;Wang et al 2009;Kraus et al 2010). …”
Section: Gap Detection Performance In the Control Micesupporting
confidence: 91%
See 4 more Smart Citations
“…As shown in Figure 2, the overall fluctuations of (G + S)/S ratios were not significantly different (F(4,50)=0.14, p=0.966) when measured at different time points. Consistent with other studies, our control group of mice exhibit robust gap-induced inhibition of the startle response (Turner et al 2006;Yang et al 2007;Wang et al 2009;Kraus et al 2010). …”
Section: Gap Detection Performance In the Control Micesupporting
confidence: 91%
“…Previous studies have shown that acoustic trauma can induce tinnitus symptoms in 56% (Kraus et al 2010) to 75% (Wang et al 2009) of exposed rats. There are three possible factors that may contribute to this inconsistency.…”
Section: Figmentioning
confidence: 96%
See 3 more Smart Citations